MULTIPLE PINEAL CYSTS ASSOCIATED WITH AN EPENDYMAL CYST PRESENTING WITH INFANTILE SPASM - (:unkn) unknown (SPRINGER VERLAG, 1995)
We present a unique case of infantile spasm in a patient with multiple pineal cysts associated with an ependymal cyst. Such a morphological etiology, to our knowledge, has not been described for patients with infantile spasm. Although postoperative neuroradiological studies demonstrated satisfactory surgical results, the patient continued to have seizures.
Keywords: BRAIN CYSTS; PINEAL CYST; EPENDYMAL CYST; INFANTILE SPASM; SYMPTOMATIC GLIAL CYSTS; GLAND